Preserving National Slang with Mobile Technology - Aldhaen, Fatima Saleh (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2017)
Arabic language and national slangs are really in danger since they ae starting to fade lately due to the globalization era that we are facing nowadays; Englishhas become the most dominating language in the Middle East since it becomes the lingua franca of education, media and commerce particularly in the gulf region. Unfortunately the misconception of not using national slangs in daily live conversations is very noticeable due to the new western educational systems and media outlets. Preserving national slangs is very crucial and important to protect our language from vanishing by using mobile technology to teach the indigenous people their national slangs and even those who are expatriates who wish to learn a certain national slang through mobile learning. The main purpose of this paper is to demonstrate a new free educational application called Bahraini slang dictionary based on Bahraini slang only, BSD comes with two languages (Arabic and English) in addition to audio pronunciation.